2020
DOI: 10.1093/schbul/sbz132
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Extracellular Free-Water in a Multicentric First-Episode Psychosis Sample, Decrease During the First 2 Years of Illness

Abstract: Abstract Recent diffusion imaging studies using free-water (FW) elimination have shown increased FW in gray matter (GM) and white matter (WM) in first-episode psychosis (FEP) and lower corrected fractional anisotropy (FAt) in WM in chronic schizophrenia. However, little is known about the longitudinal stability and clinical significance of these findings. To determine tissue-specific FW and FAt abnormalities in FEP, as part of a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
5
15
0
Order By: Relevance
“…These data suggest that the earlier stages of illness in schizophrenia may be characterized by pathologies that affect the extracellular space. Our work directly aligns with previous reports and a recent meta-analysis [34] showing widespread FW elevations in early course schizophrenia populations [9,10,12,13] and an attenuated FW pathology in individuals with a longer duration of illness [14][15][16][17][18]. This study expands upon those previous studies using our well-matched sample of healthy controls and participants with schizophrenia, thus enabling us to characterize the relationships between FW, age and duration of illness, separately.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data suggest that the earlier stages of illness in schizophrenia may be characterized by pathologies that affect the extracellular space. Our work directly aligns with previous reports and a recent meta-analysis [34] showing widespread FW elevations in early course schizophrenia populations [9,10,12,13] and an attenuated FW pathology in individuals with a longer duration of illness [14][15][16][17][18]. This study expands upon those previous studies using our well-matched sample of healthy controls and participants with schizophrenia, thus enabling us to characterize the relationships between FW, age and duration of illness, separately.…”
Section: Discussionsupporting
confidence: 88%
“…Since then, four additional studies have identified increased FW in independent early psychosis cohorts [10][11][12][13], thereby calling into question whether the biological changes taking place in the early stages of illness are in fact driven by structural changes in white matter, as previously assumed by earlier DTI studies [1][2][3][4][5]. All five published studies have observed FW increases in cerebral white matter [9][10][11][12][13], with two studies also observing FW elevations in gray matter [9,11]. Moreover, two of these studies, Guo et al…”
Section: Introductionmentioning
confidence: 92%
“…of patients Patient age, Mean (SD), y Patient gender, % male DSM diagnoses Disease status (FEP, CSZ) Duration of illness (months), Mean (SD) PANSS total score Mean (SD) No. of controls CPZ equivalent, Mean (SD) Type of scanner Neuroimaging ROIs Pasternak et al [ 24 ] United States of America (USA) 18 21.6 (4.3) 77.8 Schizophrenia, schizoaffective, or schizophreniform FEP 6.2 (4.3) 79(20) 20 472.2 (651.3) 3 T Whole-brain Berge et al [ 34 ] Spain, The Netherlands 59 22.1 (5.9) 64.4 Schizophrenia, schizoaffective, or schizophreniform FEP 4.6 (3.3) 82.3 (27.6) 101 527.5 (409.4) 3 T, 1.5 T Whole-brain Lesh et al [ 29 ] USA 36 21.4 (3.4) 69.4 Schizophrenia, schizoaffective, or schizophreniform FEP Not reported 84 (19) 40 226.6 (168.7) 3 T Whole-brain Lyall et al [ 35 ] USA 63 21.4 (4.9) 73 Schizophrenia, schizoaffective, or schizophreniform FEP Not reported 79 (14) 70 Not reported 3 T Whole-brain Mandl et al [ 30 ] The Netherlands/USA 40 26.8 (5.8) 92.5 Schizophrenia CSZ 25.1 (17.4) 62.3 (15.8) 40 Not reported 1.5 T Bilateral uncinate, bilateral arcuate fasciculus, bilateral inferior lo...…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on the studies that included patients with the diagnosis of first episode of psychosis, three studies [ 24 , 34 , 35 ] found differences in FW levels between early onset patients and healthy volunteers. The only study that did not find a difference [ 33 ] used a scanner with a lower magnetic field (1.5 T), which may have reduced the sensitivity to detect differences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation